The Influence of Website Quality, Social Media, and Brand Ambassadors on Online Purchasing Decisions at Shopee Through E-Word of Mouth as An Intervening Variable in Residents of Citra Indah City Jonggol Housing - Rahayu Lestari; Natalia Pricilia Ticoalu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of Website Quality, Social Media, and Brand Ambassador on Purchase Decisions and to find out E-Word Of Mouth in intervening the relationship between Website Quality, Social Media, and Brand Ambassadors on Purchase Decisions. The population of this research is all residents of Citra Indah City Jonggol Housing. Data were collected as many as 174 respondents and processed with IBM AMOS software version 24. The results of the research conclusions: 1) Website quality directly has a positive effect on E-WOM; 2) Social Media directly has a positive effect on E-WOM; 3) Brand Ambassadors directly have a positive effect on E-WOM; 4) Website quality directly has a positive effect on Purchase Decisions; 5) Social Media directly has a positive effect on Purchase Decisions; 6) Brand Ambassador directly has a positive and insignificant effect on Purchase Decisions; 7) E-WOM directly has a positive effect on Purchase Decisions; 8) Website quality indirectly has a positive effect through E-WOM on Purchase Decisions; 9) Social Media indirectly has a positive effect through E-WOM on Purchase Decisions; 10) Brand Ambassador indirectly has a positive and insignificant effect through E-WOM on Purchase Decisions.